Early cortico-muscular coherence and cortical network changes in Parkinson’s patients treated with MRgFUS - Visani, Elisa; Panzica, Ferruccio; Franceschetti, Silvana; Golfrè Andreasi, Nico; Cilia, Roberto; Rinaldo, Sara; Rossi Sebastiano, Davide; Lanteri, Paola; Eleopra, Roberto (Frontiers in Neurology, 2024)
To investigate cortical network changes using Magnetoencephalography (MEG) signals in Parkinson's disease (PD) patients undergoing Magnetic Resonance-guided Focused Ultrasound (MRgFUS) thalamotomy.Methods: We evaluated the MEG signals in 16 PD patients with drug-refractory tremor before and after 12-month from MRgFUS unilateral lesion of the ventralis intermediate nucleus (Vim) of the thalamus contralateral to the most affected body side. We recorded patients 24 hours before (T0) and 24 hours after MRgFUS (T1). We analyzed signal epochs recorded at rest and during the isometric extension of the hand contralateral to thalamotomy. We evaluated cortico-muscular coherence (CMC), the out-strength index from non-primary motor areas to the pre-central area and connectivity indexes, using generalized partial directed coherence. Statistical analysis was performed using RMANOVA and post-hoc t-tests.Results: Most changes found at T1 compared to T0 occurred in the beta band and included: (1) a readjustment of CMC distribution; (2) a reduced out-strength from non-primary motor areas towards the precentral area; (3) strongly reduced clustering coefficient values. These differences mainly occurred during motor activation and with few statistically significant changes at rest. Correlation analysis showed significant relationships between changes of out-strength and clustering coefficient in non-primary motor areas and the changes in clinical scores.Discussion: One day after MRgFUS thalamotomy, PD patients showed a topographically reordered CMC and decreased cortico-cortical flow, together with a reduced local connection between different nodes. These findings suggest that the reordered cortico-muscular and cortical-networks in the beta band may represent an early physiological readjustment related to MRgFUS Vim lesion.